Prophylactic administration of lecithinized superoxide dismutase for a murine model of oxaliplatin-induced myelosuppression - Shimoda, Mikako; Yamaguchi, Akari; Shikata, Ayano; Murakami, Yusuke; Kawahara, Masahiro; Mizushima, Tohru; Tanaka, Ken-ichiro (Frontiers in Pharmacology, 2025)
BackgroundOxaliplatin, in combination with 5-fluorouracil and leucovorin, is a standard treatment for colorectal cancer and shows high efficacy. However, oxaliplatin induces side effects, such as chemotherapy-induced peripheral neuropathy and myelosuppression, which may lead to dose reduction, temporary drug withdrawal, or discontinuation. Lecithinized superoxide dismutase (PC-SOD) is a drug delivery system formulation with improved blood stability and tissue affinity for SOD. A phase II clinical trial of PC-SOD for chemotherapy-induced peripheral neuropathy has been conducted, and its efficacy has been confirmed for certain parameters.MethodsIn this study, we focused on myelosuppression, a major side effect of oxaliplatin, and aimed to elucidate the preventive effect of PC-SOD in a murine model of myelosuppression.ResultsOxaliplatin administration decreased the white blood cell, platelet, and red blood cell counts and hemoglobin levels in the whole blood of mice. PC-SOD treatment significantly restored the oxaliplatin-dependent reduction in white blood cell count (day 10). The gene expression of cytokines involved in hematopoietic progenitor cell differentiation and proliferation, including colony-stimulating factor (CSF)2, CSF3, interleukin (IL)-3, IL-4, IL-5, IL-6, IL-9, and stem cell factor, was also decreased by oxaliplatin administration. In contrast, PC-SOD treatment markedly restored the gene expression of these cytokines. In vivo imaging analysis showed that oxaliplatin treatment enhanced reactive oxygen species (ROS) production in the femur and tibia, whereas PC-SOD significantly suppressed this production. Furthermore, analysis of mouse-derived bone marrow cells revealed that PC-SOD suppressed oxaliplatin-induced cytotoxicity and ROS production in vitro.ConclusionThese results suggest that PC-SOD exerts an antioxidant effect and prevents oxaliplatin-induced myelosuppression, particularly in a murine model of leukopenia.